Sovereign Debt Issuance and Transformation of the Monetary Architecture in Prussia and the German Empire, 1740-1914 - Steffen Murau (Dezernat Zukunft e.V., 2023)
This paper traces the transformation of the monetary architecture and concomitant sovereign debt issuance practices in Prussia and the German Empire from 1740 to 1914 in order to reflect on contemporary ideas regarding the appropriate relation between states' treasuries, central banks, and the private banking system in matters of sovereign debt issuance. It discusses three institutions as "protagonists" - the Königlich Preußische Bank, the Seehandlung, and the Disconto-Gesellschaft - and follows them through four phases of Prussian and German history: feudal Prussia from Friedrich II to the defeat against Napoleon (1740-1806); from the Stein-Hardenberg reforms to the March Revolution (1807-1848); post-revolutionary Prussia, including the rise of Bismarck, his three wars, and the foundation of the German Empire (1849-1871); and Prussia in the German Empire during the first era of globalization (1871-1914). Adopting the Monetary Architecture framework as a conceptual lens, the analysis yields three main findings. First, off-balance-sheet fiscal agencies (OBFAs) have played a key role in the issuance and management of sovereign debt, even before central banks and treasuries in the modern sense had formed. This is highlighted in the institutional role of the Seehandlung, which kick-started Prussian sovereign debt issuance during the Napoleonic Wars. Second, central banking institutions have historically shifted within the public-private spectrum. The state-owned Königlich Preußische Bank became more functional and accountable after it was converted into the hybrid Preußische Bank. When it was transformed into the Reichsbank in 1875, a fully private ownership structure was chosen. Third, the economic liberalization after 1848 and the increased need to harness private funding for war finance led to the emergence of syndicated sovereign bond issuance. The Disconto-Gesellschaft, which played a leading role in the Prussia Consortium and the Imperial Bond Consortium, was at the forefront of establishing a new relationship between private finance and the state.
Keywords: 330; Fiscal Policy; Debt; Institutions; History